The Impact of PBL-STEM Model on Student Motivation and Achievement in IPAS Learning at Elementary School - Imron, Zaini; Nuriman, Nuriman; Aritsya Putera, Pramudya Dwi (ATTA`DIB, 2025)
This study aims to determine the effect of the STEM-based Problem-Based Learning (PBL) model on students' motivation and learning outcomes in IPAS (Natural and Social Sciences) subjects at SD Negeri Gelang 05. A quasi-experimental method with a pretest-posttest control group design was used. The research sample consisted of two classes of 25 students each, divided into an experimental group and a control group. Instruments included a learning motivation questionnaire, achievement tests, observation sheets, interview guides, and documentation. Data were analyzed using normality tests, homogeneity tests, and independent sample t-tests with the help of SPSS 16.0. The results showed a significant difference between the experimental and control classes in both motivation and learning outcomes. Students in the experimental class scored higher on average in both areas compared to those in the control class. These findings indicate that the STEM-based PBL model is effective in enhancing students' motivation and learning outcomes. It is recommended as an innovative learning approach for IPAS instruction in elementary schools.